A novel green approach for the preparation of high performance nitrile butadiene rubber-pristine graphene nanocomposites. (15th October 2019) - Thomas, Bony; Maria, Hanna J.; George, Gejo; Thomas, Sabu; Unnikrishnan, N.V.; Joseph, Kuruvilla
Abstract: Present article scrutinizes the effect of pristine few layers graphene incorporation into NBR matrix via a green approach in terms of mechanical properties and two different fabrication routes viz. latex casting and latex casting followed by dry rubber mixing. Large scale production of pristine few layers graphene was accomplished by means of planetary ball milling and was characterized using X-ray diffraction (XRD), Raman spectroscopy and Transmission electron microscopy (TEM) analysis. The produced graphene and procured MWCNT was then successfully incorporated (separately) into NBR latex. It was found out that at a particular filler loading of 3 phr for latex casting method, 5 phr for dry rubber mixing method and only 0.4 phr for MWCNT based samples the produced nanocomposites demonstrated a significant increment in tensile properties. However, when only the supernatant from the 3 phr graphene dispersion was used, the sample showed an improved increment (363%) in mechanical properties due to the removal of other bulk particles during settling which might otherwise act as stress concentrators inside the composite. The demand for multifunctional elastomers is increasing now a day and hence these findings where pristine graphene has been successfully and uniformly incorporated into NBR matrix (an important synthetic elastomer with huge applications) would be scientifically significant. Graphical abstract: Image 1